Digital database and mapping of pulse crops in the temperate areas of Jammu region - Singh, G; Sharma, L K; Ojha, S (Plant Science Today, 2025)
Pulses are environmentally friendly, low in fat, calories, and salt, and rich in resistant starch, dietary fibre, minerals, and vitamins. They can thrive under stressful conditions and are often referred to as the "poor man's meat". With their low glycemic index, pulses help regulate blood sugar levels, making them beneficial for diabetes management. Additionally, they contribute to environmental sustainability by requiring less water and synthetic fertilizers, than other crops, while enhancing soil fertility through nitrogen fixation. Incorporating pulses into diets supports human health and promotes environmental sustainability, underscoring their importance in addressing food security and fostering sustainable agricultural practices. India leads global pulse production, contributing 25% to the total pulse production. In the Jammu and Kashmir (J&K) region, 12,955 acres and 5,938 hectares are reportedly dedicated to pulse cultivation. According to digital database mapping, 98% of respondents in the study area cultivated Rajma, followed by black gram (79%), green gram (76%), horse gram (21%), French bean (19%), and red lentil (15%). The study revealed that all respondents used farmyard manure as a nutrient source, though application rates varied across regions and crop types. Hand weeding was the preferred weed control method across all farms. The findings also highlight a strong preference among farmers for organic farming over conventional methods, with many advocating for the increased promotion of organic practices. This research explores the current state of pulse production technologies, identifies limitations affecting their cultivation, and strategies to enhance productivity.